The role of institutional arrangement in the development of the agro-processing sector (2011-2015) - Moyo, Cynthia (My University, 2020)
The study unpacks institutional arrangements which were available when developing the agro-processing manufacturing sector with the milling industry as a case study in the period 2011-2015. In-depth interviews were conducted with the respondents from five institutions (DTI, DAFF, IDC, NAMC and GDARD), FABCOS and Old Mutual Masisizane Fund respondents did not owner the interview invitation which led to the study relying more on secondary data. The key findings revealed that there are common factors that have been contributing to the inefficiencies in policy implementation which includes territorial disputes and policy inconsistency. The study also learnt that there were no concrete institutional arrangements on the ground, thus the network was weak or non-existent. Issues of coordination, information sharing, business practices and moral hazard among the few factors contributed to little or no current visible successes to date which led to policy and network failure. Therefore, industrial policy durations must be introduced to the project at planning phase to avoid lack of participation at implementation phase. Involved institutions need to understand and play their roles rather than focus on how well institutional arrangement is integrated to avoid weak network systems (Provan & Milward, 1995). The institutional arrangements between government and private sector need to be strengthened to avoid or minimize poor business practices on entrepreneurs once they have received funding. Thus, within network systems, mentoring institution need to be included to ensure that businesses are run effectively. Moreover, government need to work together with DFIs for funding purposes as this will ensure that their priority areas are also considered by DFIs when identifying their strategic areas. Agricultural policies must be drafted together with industrial policies because both policies strive to contribute to the national long-term vision such as job creation, poverty alleviation and reduction in inequality (Briones & Felipe, 2013)
The role of institutional arrangement in the development of the agro-processing sector in South Africa
A research report submitted to the Faculty of Commerce, Law and Management of the University of the Witwatersrand, Johannesburg in partial fulfilment of the requirements for the degree of Masters of Management in Public Policy (MM-PP), 2020
Keywords: UCTD; Agro-processing; Manufacturing sector; DTI; DAFF; NAMC; IDC; GDARD; INSTITUTIONAL ARRANGEMENT; SDG-12: Responsible consumption and production; SDG-15: Life on land